Blockchain for Secure and Transparent SAP Transactions in Financial Institutions in Indonesia - Judijanto, Loso; Elisabeth, Christine Riani (West Science Nature and Technology, 2025)
The integration of blockchain technology into SAP transactions holds significant potential to enhance security and transparency within financial institutions in Indonesia. This study employs a qualitative approach, using interviews with six key informants, to explore the challenges, benefits, and practical implications of this technological innovation. Findings reveal that blockchain’s decentralized, immutable, and encrypted architecture addresses critical security concerns, while its transparent ledger fosters accountability and trust among stakeholders. However, challenges such as high implementation costs, technological complexity, and regulatory uncertainty pose significant barriers to adoption. Practical recommendations include phased deployment, collaborative partnerships, and proactive regulatory engagement. This research underscores blockchain's transformative potential for Indonesia’s financial sector, offering a pathway to robust, secure, and transparent financial operations.